MET1 Is a Thylakoid-Associated TPR Protein Involved in Photosystem II Supercomplex Formation and Repair in Arabidopsis. Issue 1 (13th January 2015) - Bhuiyan, Nazmul H.; Friso, Giulia; Poliakov, Anton; Ponnala, Lalit; van Wijk, Klaas J.
Abstract : TMET1 is a thylakoid-associated protein that functions in assembly of PSII complexes and interacts with PSII core proteins CP43 and CP47. Abstract: Photosystem II (PSII ) requires constant disassembly and reassembly to accommodate replacement of the D1 protein. Here, we characterize Arabidopsis thaliana MET1, a PSII assembly factor with PDZ and TPR domains. The maize ( Zea mays ) MET1 homolog is enriched in mesophyll chloroplasts compared with bundle sheath chloroplasts, and MET1 mRNA and protein levels increase during leaf development concomitant with the thylakoid machinery. MET1 is conserved in C3 and C4 plants and green algae but is not found in prokaryotes. Arabidopsis MET1 is a peripheral thylakoid protein enriched in stroma lamellae and is also present in grana. Split-ubiquitin assays and coimmunoprecipitations showed interaction of MET1 with stromal loops of PSII core components CP43 and CP47. From native gels, we inferred that MET1 associates with PSII subcomplexes formed during the PSII repair cycle. When grown under fluctuating light intensities, the Arabidopsis MET1 null mutant ( met1 ) showed conditional reduced growth, near complete blockage in PSII supercomplex formation, and concomitant increase of unassembled CP43. Growth of met1 in high light resulted in loss of PSII supercomplexes and accelerated D1 degradation. We propose that MET1 functions as a CP43/CP47 chaperone on the stromal side of the membrane during PSII assembly and repair. This function is consistent with the observed differential MET1 accumulation across dimorphic maize chloroplasts.